Socialization of The Use of BPJS for Services Inpatient Care at Pagar Jati Health Center Lubuk Pakam District - Kasim, Felix; Br Ginting, Luci Riani (JURNAL PENGMAS KESTRA (JPK), 2024)
The national health insurance program is integrated into the Health Social Security Administering Body (BPJS Health). Through BPJS Health, the government is trying to ensure that all Indonesian citizens have fair and equitable access to quality health services without being constrained by costs. This program covers a variety of health services, from preventive services to treatment, with the hope of improving the welfare and health of the community as a whole. The JKN program is integrated into the Health Social Security Administering Agency (BPJS Health), a public legal entity that aims to administer the JKN program for all Indonesian people. This activity aims to provide health education about the use of BPJS for inpatient health services at the Pagar Jati Health Center. The method for carrying out activities is using observation sheets and questionnaires about the benefits of BPJS. From the results of the counseling provided, there was a significant increase in services, namely 86% compared to before the intervention was given.  This indicates that the differences in the predisposing factors of BPJS patients significantly influence the utilization of inpatient services at the Pagar Jati Community Health Center. There is a significant influence on respondents' knowledge before and after being given counseling about the use of BPJS for inpatient services at the Pagar Jati Community Health Center, this can be seen from the percentage level knowledge before and after with a small percentage having insufficient knowledge. From the results of activities carried out by BPJS user patients, they were very enthusiastic about welcoming this activity. Through this activity, it is hoped that knowledge of the use of BPJS will increase so that you will no longer hesitate to use the BPJS card for inpatient health services at the Pagar Jati Community Health Center.